Evaluación del impacto del Covid 19 en la economía de la “Corporación Fortaleza del Valle” periodo 2019-2020 - Barre Zambrano, Yonny Joselito (2023)
The objective of this work was to determine the impact of covid 19 on the economy of the Fortaleza del Valle Corporation for the 2019-2020 period as a contribution to its business redirection. For this, analytical, quantitative, qualitative and expert methods were used, which facilitated the research process, allowing the use of thought to execute deductions, analysis and synthesis. In addition, as techniques, observation, SWOT analysis, PEST analysis, interview and Delphi technique, which served to approach the facts and access their knowledge and instruments were used to obtain information such as, observation sheet, interview guide and SWOT matrix. As a result, it was obtained that only 33% of the organization's assets were being financed by third parties, while by 2020 it decreased to 31%. While for the sales turnover indicator for the year 2019, it was 0.80, which means that the organization for every dollar it invests in assets generates 0.80 cents in sales; while for 2020 there was a minimum increase in this item of 0.93, for every dollar invested it generates 0.93 cents in sale. It is concluded that for both years 2019-2020, the corporation had sufficient liquidity for short-term obligations, solvency in terms of financial leverage, management indices were managed properly, and it presents a positive gross margin in both years, but there is evidence of a ROA, ROE and negative net margin, due to its high operating expenses in 2019, reducing for 2020.